Association between advanced maternal age and adverse pregnancy outcome - R., Anusuya; T., Uma; M., Arun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: AMA (advanced maternal age) is associated with a wide range of adverse pregnancy outcomes. The purpose of this study is to review the impact of maternal age on a range of adverse pregnancy outcomes in order to assist in accurate counselling of women considering delaying pregnancy or those who are already pregnant and concerned about the risk of developing complications due to their age. Methods: The present study is a prospective cohort study conducted in Sree Avittom Thirunal Hospital, Medical College, Thiruvananthapuram, India. The study population was divided into two groups. The exposure cohort included 200 elderly pregnant women (at or above 35 years). The control cohort included 200 younger women (<35 years). The two groups were followed up throughout their pregnancy period and pregnancy outcomes studied. Results: The mean age of the study group was 37.1 years while the mean age of the control group was 25.2 years. Induction rates were higher among younger gravidae (50%) while Caesarean before labour was higher (p<0.001) in the elderly. Preterm delivery and Caesarean sections were higher (p<0.001) in the study group. However primary CS rates were higher in the control group. PPH was significantly higher (p 0.019) in the elderly group. Conclusions: It is concluded in the present study that women with advanced maternal age are at higher risk of developing complications during and after delivery. Effective counselling should be given to mothers who plan to delay childbirth.